Examination of Academic Human Resource Management Policies of Private Special Education Institutions and Rehabilitation Centers - Cengiz Alper Karadağ; Nazife Karadağ (Uluslararası Türk Eğitim Bilimleri Dergisi)
This research aims to examine the human resource management policies of private special education institutions and rehabilitation centers based on the managers’ views. The basic qualitative research design was adopted in the research. The participants of the study consisted of managers of private special education institutions and rehabilitation centers operating in the province of Adıyaman. Criterion sampling technique was adopted in determining the participants. In this context, semi-structured interviews were conducted with 15 managers of private special education institutions and rehabilitation centers. The data obtained from the interviews with managers has been analyzed through content analysis. In the research, the opinions of the institution managers regarding the teacher employment process of their institutions were discussed under the themes of "employment criteria“, “employment process," and "problems encountered in the employment process." Policies for teacher development were examined under the themes of "personal development" and "professional development", while policies for teacher integration were examined under the themes of "rewarding". Policies for teacher evaluation were studied under the themes of "in-house evaluation" and "external evaluation". According to research results, the policies that shape the employment process are related to the nature of pre-service education and the professional and academic qualifications of teacher candidates. Additionally, based on the views of school administrators, it has been concluded that the shortage of subject experts is one of the problems encountered in the human resources management process of teacher employment. However, it has been stated that career planning and policies for professional development are insufficient in the process of teacher training and development, and teacher evaluation policies are shaped within the framework of internal and external evaluation criteria.